Parâmetros genéticos e seleção combinada para a concentração de minerais, compostos fenólicos e caracteres da qualidade tecnológica em linhagens de feijão andino - Mezzomo, Henrique Caletti (2019)
The estimation of genetic parameters contribute to the knowledge of the behavior of characters of biofortification and technological quality in Andean beans, aiding in the development of biofortified cultivars and with acceptance in the consumer market. Thus the objectives of this work were: (1) to verify if there is genetic variability for the concentrations of the minerals potassium, phosphorus, magnesium, calcium, iron and zinc; for the concentration of phenolic compounds; and for technological quality characters, color parameters (L*, a* and b*) and mass of 100 grains of Andean beans strains; (2) to analyze the inheritance pattern of macro and microminerals concentration, phenolic compounds and characteristics that confer technological quality on Andean beans in generation F5:6 and F5:7; (3) to obtain estimates of heritability and gain with the selection for micromineral macro and micromin concentration, phenolic compounds and characteristics that confer technological quality on Andean bean grains; (4) select Andean beans lines with high nutritional and technological quality. To do so, Andean bean strains obtained from the cross between the cultivars Hooter x Cal 96 were evaluated. Two field experiments were conducted in the experimental area of the Bean Breeding Program of the Federal University of Santa Maria, Santa Maria - RS. In the 2017/18 crop, the experiment was conducted in an expanded block design and 61 treatments were evaluated, 57 of the F5:6 lineages, the two parental and the Pérola and Iraí cultivars. The experiment conducted in the second half of the year, conducted in the 8 x 8 simple lattice design, evaluated a total of 64 treatments, being 52 lines of the F5:7 generation, the two parental and eight bean cultivars. Genetic variability, transgressive segregation and quantitative inheritance pattern were observed for all evaluated minerals and 100 grain mass. For the coloring parameters (L*, a* and b*) a qualitative inheritance pattern was identified. High heritability was observed for potassium, phosphorus, magnesium, calcium, iron, zinc in grains in the F5:6 generation, already in the F5:7 generation was high heritability for magnesium, calcium and iron, and intermediate magnitude for potassium concentration, phosphorus and zinc in the grains. For the concentration of phenolic compounds, L*, a* and b* and mass of 100 grains independent of the evaluated generation, high heritability was observed. Cranberry type genotypes should have L* greater than 52, and of mottled type should have L* less than 37. Lineages 46-18 have high concentrations for macrominerals and low concentration of phenolic compounds and will be selected by the biofortification program. As well as the lines DFA 04-18 and DFA 05-18 have high concentration of potassium, phosphorus and phenolic compounds. Also the lineage with cream integument and red rajas DFA 01-18 and the line of red integument and rajas cream DFA 12-18 are biofortified for iron and zinc, they have pattern of color and size of grains. These should be selected by the breeding program.